Autenticidad y alienación: Disonancias ideológico-culturales entre la "nueva canción" chilena y el rock anglosajón. - Pino-Ojeda, Walescka (Studies in Latin American Popular Culture, 2015)
The ideological polarization that framed the Cold War period (1945-1989) affected not only international relations but also the social commitments and aesthetic options of those artists and cultural activists who instigated the Latin American decolonization processes of the 1960s and 1970s. In this framework, the positivistic signature of the socialist-capitalist divide drove the decolonizing forces of the region to mistrust any form of popular culture produced from the industrial capitalist centers of power. Anglo-American rock was generally perceived as working against facilitating social class awareness. This article investigates the points of convergence and disagreement between these two movements, paying special attention to Violeta Parra and Víctor Jara's aesthetic and ethical viewpoints, both of whom are foundational and emblematic members of the Chilean "nueva canción" movement.